A readout electronic system for a 3D position-sensitive CdZnTe gamma-ray spectrometer based on the CPRE10-32 readout ASIC. (1st October 2022) - Chen, Tianze; Li, Xiaohui; Wang, Ke; Wei, CunFeng; Shuai, Lei; Jiang, Xiaopan; Wang, Na; Wang, Mian; Wei, Long
Abstract: A readout electronic system based on the Charge Pulse Readout Electronics 10-32 (CPRE10-32) Application Specific Integrated Circuit (ASIC) has been developed for the 3D position-sensitive CdZnTe gamma-ray spectrometer. The system includes the Font-end Electrics (FEE) board, the Data Acquisition (DAQ) board, the FPGA firmware, and the PC software. The Full Width at Half Maximum (FWHM) of the electronic noise of the system was approximately 4.72 keV when the 3D-CZT detector and high voltage were connected and the minimum gain was selected. The electronic noise at the minimum and maximum gain using the calibration signal without the detector was approximately 3.335 keV and 3.074 keV, respectively. The Equivalent Noise Charge Number (ENN) was about 375 e - with the detector and about 265 e - with the detector. The test data of Cs-137 demonstrated that the linear response range of the system reached up to 3 MeV and 450 keV at the minimum and maximum gain, respectively. With the 3D-CZT detector, the Am-241 and Cs-137 radioactive sources were detected, and the energy resolution was 7.25% and 2.22%, respectively. By performing electron drift time correction, the energy resolution of the full-energy peak of Cs-137 at 662 keV was improved to 0.76% at medium gain. After acquiring energy and time data successfully, it is demonstrated that this readout electronic system can meet the hardware requirements for Compton scatter imaging with 3D-CZT.